Accounting - Horngern, Charles T. (Prentic - Hall bInternatioanl, 2002)
The authors of ACCOUNTING, 23e, understand that you need to find important information quickly. This textbook uses an integrated learning system to help you complete homework and lead you to accounting mastery. Building on the authors' proven approach, clear examples and high-impact writing guide you through the preparation of financial statements as the authors artfully provide a framework for understanding what accounting is all about and accounting's evolving role in business.